Ultrasound guided platelet rich plasma injections for post-traumatic greater occipital neuralgia following concussion: a pilot randomized controlled trial - Stone, Jacqueline E.; Campbell, Christina; Tabor, Jason B.; Bonfield, Stephan; Machan, Matthew; Shan, Rodney Li Pi; Debert, Chantel T. (Frontiers in Neurology, 2024)
Background Treatment for post-traumatic greater occipital neuralgia (GON) includes serial injections of steroid/anesthetic. While these injections can alleviate pain, effects can be transient, frequently lasting only 1 month. As a potential alternative, platelet-rich plasma (PRP) injections are an emerging biological treatment with beneficial effects in peripheral nerve disorders. We investigated the feasibility, safety, and effectiveness of a single PRP injection for post-traumatic GON in comparison to saline or steroid/anesthetic injection. Methods In this pilot randomized, double-blinded, placebo-controlled trial, 32 adults with post-traumatic GON were allocated 1:1:1 to receive a single ultrasound-guided injection of (1) autologous PRP (2) steroid/anesthetic or (3) normal saline. Our primary outcome was feasibility (recruitment, attendance, retention) and safety (adverse events). Exploratory measures included headache intensity and frequency (daily headache diaries) and additional questionnaires (headache impact, and quality of life) assessed at pre-injection, 1 week, 1 month, and 3 months post-injection. Results We screened 67 individuals, 55% were eligible and 95% of those participated. Over 80% of daily headache diaries were completed with 91% of participants completing the 3-month outcome questionnaires. No serious adverse events were reported. There were no significant differences between groups for headache intensity or frequency. Headache impact on function test-6 scores improved at 3 month in the PRP (β = −9.7, 95% CI [−15.6, −3.74], p = 0.002) and saline (β = −6.7 [−12.7, −0.57], p = 0.033) groups but not steroid/anesthetic group (p = 0.135). Conclusion PRP is a feasible and safe method for treating post-traumatic GON with comparable results to saline and steroid/anaesthetic. Further trials with larger sample sizes are required. Clinical trial registration:https://clinicaltrials.gov/, identifier NCT04051203.